2021
DOI: 10.1021/jacs.1c05521
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Kadcoccinic Acid A Trimethyl Ester

Abstract: The first total synthesis of the trimethyl ester of kadcoccinic acid A is described. The central structural element of our synthesis is a cyclopentenone motif that allows the assembly of the natural product skeleton. A gold­(I)-catalyzed cyclization of an enynyl acetate led to efficient construction of the cyclopentenone scaffold. In this step, optimization studies revealed that the stereochemistry of the enynyl acetate dictates regioisomeric cyclopentenone formation. The synthesis further highlights an effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…As an example, when a less functionalized enoate was needed for total synthesis of ent-phaeosphaeride A (Scheme 1c), 8 a polyfluorophosphonate reagent was used to convert an aldehyde to a Z-α-methyl carboxylic ester, which was then subjected to catalytic dihydroxy addition. A common way of accessing an aldehyde, which may be used for such reactions, is by oxidative cleavage of the trisubstituted alkene within a naturally occurring feedstock compound; the approaches involving geraniol and citronellol en route to transtaganolide B, 9 isomintlactone, 10 and kadcoccnic acid triester 11 are representative (Scheme 1c).…”
Section: Introductionmentioning
confidence: 99%
“…As an example, when a less functionalized enoate was needed for total synthesis of ent-phaeosphaeride A (Scheme 1c), 8 a polyfluorophosphonate reagent was used to convert an aldehyde to a Z-α-methyl carboxylic ester, which was then subjected to catalytic dihydroxy addition. A common way of accessing an aldehyde, which may be used for such reactions, is by oxidative cleavage of the trisubstituted alkene within a naturally occurring feedstock compound; the approaches involving geraniol and citronellol en route to transtaganolide B, 9 isomintlactone, 10 and kadcoccnic acid triester 11 are representative (Scheme 1c).…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies demonstrated that the carbocyclization could be combined with sequential oxidative cleavage of the exocyclic olefin to afford the ketone 9 in 51% overall yield on gram scale (Scheme ). The installation of the challenging gem -dimethyl motif in ketone 11 was accomplished by Eschenmoser methylenation followed by reductive alkylation to avoid the problematic epimerization of the β-hydrogen at C5, which was reported in the previous racemic total synthesis . The exocyclic methylene unit of (+)-zizaene ( 12 ) was then installed using a one-step Peterson olefination reaction in 54% yield, which avoided a high temperature Wittig reaction that also has the potential to epimerize C5.…”
mentioning
confidence: 99%
“… 4 In this regard, the gold-catalyzed cycloisomerization of vinylallenes depicted in Scheme 1 A deserves special mention, as it has evolved as one of the most reliable and useful methodologies for accessing highly substituted cyclopentadienes, 5 , 6 even in the challenging scenarios of the total synthesis of complex natural products. 7 Mechanistically, this transformation is proposed to proceed through initial coordination of the vinylallene to the cationic gold(I) catalyst through the central carbon of the allene moiety, 8 leading to a pentadienyl cation intermediate, which then would undergo a Nazarov-like cyclization to give a cationic gold(I)-carbenoid intermediate. A final 1,2-hydrogen (or alkyl, in the case of 1,1-dialkyl-substituted substrates) shift would render the final cyclopentadiene derivative with regeneration of the cationic gold catalyst.…”
mentioning
confidence: 99%
“…Relevant examples include the gold-catalyzed cyclization of ynamides and gold carbenoid precursors such as propargyl esters and cyclopropenes . In this regard, the gold-catalyzed cycloisomerization of vinylallenes depicted in Scheme A deserves special mention, as it has evolved as one of the most reliable and useful methodologies for accessing highly substituted cyclopentadienes, , even in the challenging scenarios of the total synthesis of complex natural products . Mechanistically, this transformation is proposed to proceed through initial coordination of the vinylallene to the cationic gold­(I) catalyst through the central carbon of the allene moiety, leading to a pentadienyl cation intermediate, which then would undergo a Nazarov-like cyclization to give a cationic gold­(I)-carbenoid intermediate.…”
mentioning
confidence: 99%